Improved LDMOS‐SCR for high‐voltage electrostatic discharge (ESD) protection applications. Issue 13 (1st June 2020) - Song, Wenqiang; Hou, Fei; Du, Feibo; Liu, Jizhi; Liu, Zhiwei; Liou, Juin J.
Abstract : An improved lateral double‐diffused MOS silicon‐controlled rectifier (ILDMOS‐SCR) for high‐voltage electrostatic discharge (ESD) protection applications has been proposed and verified in a 0.18 µm 5 V/24 V BCD process. The proposed improved lateral double‐diffused MOS silicon‐controlled rectifier (LDMOS‐SCR) is constructed by adding a gated P‐type/intrinsic/N‐type (PIN) diode into a conventional LDMOS‐SCR. With part of the ESD current discharges from the surface gated PIN diode path, the proposed ILDMOS‐SCR achieves a high holding voltage of 30 V as well as a high failure current of 10.04 A, which is evaluated to pass 15 KV Human Body Model (HBM) ESD stress.